2017
DOI: 10.1021/acs.langmuir.7b03212
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Induced Structure and Molecular Dynamics in a Lipid Bilayer Membrane

Abstract: The solid-substrate-dependent structure and dynamics of molecules in a supported lipid bilayer (SLB) were directly investigated via atomic force microscopy (AFM) and single particle tracking (SPT) measurements. The appearance of either vertical or horizontal heterogeneities in the SLB was found to be strongly dependent on the underlying substrates. SLB has been widely used as a biointerface with incorporated proteins and other biological materials. Both silica and mica are popular substrates for SLB. Using sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 73 publications
7
37
0
Order By: Relevance
“…The Ra roughness of glass (0.15 nm) after piranha cleaning and UV ozone cleaning is over 4 times rougher than mica (0.03 nm) after cleavage ( Figure 5A+B). These values match closely to previous AFM roughness measurements of mica, 15,37 and piranha cleaned glass. 14 We also studied other substrates used to support lipid bilayers, including glass with a differing composition (Glass 2), quartz, silicon and thermally oxidised silicon ( Figure 2).…”
Section: Substrate Roughness Is Correlated With Domain Sizesupporting
confidence: 91%
See 2 more Smart Citations
“…The Ra roughness of glass (0.15 nm) after piranha cleaning and UV ozone cleaning is over 4 times rougher than mica (0.03 nm) after cleavage ( Figure 5A+B). These values match closely to previous AFM roughness measurements of mica, 15,37 and piranha cleaned glass. 14 We also studied other substrates used to support lipid bilayers, including glass with a differing composition (Glass 2), quartz, silicon and thermally oxidised silicon ( Figure 2).…”
Section: Substrate Roughness Is Correlated With Domain Sizesupporting
confidence: 91%
“…Whilst FCS experiments have found that there is no significant difference between DOPC diffusion on glass and mica, 12 for SLBs formed using the same vesicle fusion bilayer deposition method as in this paper, there are many varied results in the literature. 22,31,37 To verify the finding of an identical Figure S6) and in literature. 44,45 It should be noted that this is a DSC cooling scan value to match the FRAP data also collected during cooling, and that cooling rates cause an offset in Tm values away from the true value (details in SI).…”
Section: Molecular Diffusionsupporting
confidence: 61%
See 1 more Smart Citation
“…The SLBs' stability and their constrained orientation make it possible to study them using 2 surface-sensitive measurement techniques such as atomic force microscopy, particle tracking via fluorescence measurements, surface plasmon resonance, surface second harmonic generation spectrometry, neutron or X-ray specular reflectometry [5][6][7][8][9][10] . Molecular dynamics (MD) simulations can also be advantageously used to investigate SLBs, to cross-validate the results of the experimental approaches, or to provide structural and dynamical descriptions at the molecular level 5,11?…”
Section: Introductionmentioning
confidence: 99%
“…Despite the molecular insight that can be gained by numerical simulations 13,[16][17][18][19][20] , relatively few computational studies have been reported yet (see the review by Hirtz et al 21 ). Indeed, both experiments and simulations 8,[22][23][24] have highlighted how strongly the SLB properties change, depending on the interplay between the membrane/solid, membrane/solvent and solid/solvent interactions.…”
Section: Introductionmentioning
confidence: 99%